SONGKOK RECCA TO BONE; IDENTITAS LOKAL YANG MENASIONAL - Jumadi; Nurlela; Asmunandar; Khaeruddin; Andi Dewi Riang Tat; Bahri (Universitas Negeri Makassar, 2023)
This study of Songkok Recca to Bone is a study that tries to uncover the history of existence, the meaningful value of the songkok recca tersbut and the socioeconomic impact of recca songkok kerajiann for msayarakat in Paccing Village. This research as a study of local history that elevates local handicrafts as a cultural product that has economic value. The research method in this study is historical method with heuristic steps (data collection), criticism (verification), interpretation and historiography (writing). The use of the hat